Floral Motifs Design on Sarawak Traditional Malay Songket - Mohamad Morni, Asrul Asshadi; Samin, Mohd Azhar; Legino, Rafeah (Environment-Behaviour Proceedings Journal, 2021)
This study is partly an ongoing project to identify the floral motifs design on Sarawak traditional Malay songket. This project begins with a review of related literature that provides an example of textile—also supported with visual data on Sarawak traditional Malay songket gathered from the field visit, which is captured into the digital compilation. The identification process defined that the Sarawak traditional Malay songket motifs mainly develop from various floral sources reflecting and inspiring nature. This study shared different design Malay songket motifs in Sarawak and represent their tradition in textile heritage. Keywords: Malay; Motifs; Sarawak; Songket eISSN: 2398-4287© 2021. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians/Africans/Arabians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v6iSI4.2902